2012
DOI: 10.1080/14786435.2011.648377
|View full text |Cite
|
Sign up to set email alerts
|

Coupled motion of [10−10] tilt boundaries in magnesium bicrystals

Abstract: Magnesium bicrystals were grown with symmetric and asymmetric tilt boundaries about the [10-10] axis using the vertical Bridgman technique. Isothermal constant load tensile tests were conducted on these bicrystals in the temperature range 300-500 C and relative displacements of the two grains were measured to obtain an appreciation for grain boundary motion characteristics. Coupled grain boundary motion was noted in almost all cases with the degree of tangential motion versus migration changing with tilt misor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Initially observed experimentally for low-angle GBs in Zn [10,11], the coupling effect has recently been demonstrated for many high-angle GBs in a number of metallic and non-metallic materials [6][7][8][9][12][13][14][15][16][17][18][19][20]. The coupling can be responsible for the stress-induced grain growth in nano-crystalline materials [16,[21][22][23][24] and can influence the nucleation of new grains during recrystallization [25].…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…Initially observed experimentally for low-angle GBs in Zn [10,11], the coupling effect has recently been demonstrated for many high-angle GBs in a number of metallic and non-metallic materials [6][7][8][9][12][13][14][15][16][17][18][19][20]. The coupling can be responsible for the stress-induced grain growth in nano-crystalline materials [16,[21][22][23][24] and can influence the nucleation of new grains during recrystallization [25].…”
Section: Introductionmentioning
confidence: 95%
“…In fact, the impossibility of coupled motion of asymmetrical boundaries was suggested in the classical paper by Read and Shockley [46]. Yet, recent MD simulations [31,47,48], bicrystal experiments [6,9] and the observation of coupled GB motion in polycrystalline materials suggest that this may not be the case. Even less is known about geometric rules of coupling or migration mechanisms of large-angle asymmetrical GBs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the migration of asymmetric GBs was thought to be impossible, but recent observations of coupled GB motion in bicrystal experiments [25,26] has suggested that this may not be true. However, the geometric rules of coupling or migration mechanisms of asymmetric GBs are less known.…”
Section: Resultsmentioning
confidence: 99%